PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI DELICIO BAKERY CAFÉ TEBET JAKARTA - Verry Cyasmoro; Sheli puspita Anggraeni (LPPM Universitas Asa Indonesia, 2020)
The purpose of this study is to determine the effect of Price, Product quality and Promotion on Purchasing Decision. The population of this study are consumer of Delicio Bakery Café Tebet Jakarta from May up to June 2019, the sampling used is accidental sampling technique. Data collection by accidental technique using the designd questionnaire that has been tested its validity and reliability prior to distribution. Data analysis by descriptive and quantitative. The quantitative initiated by classic assumption test followed by multiple regression analysis. While model testing by F-test, t-test, coorelatioon and determination. The results showed that Price, Product quality and Promotion partially and simultaneously have a significant effect on purchasing decision.